Synthesis and Cytotoxicity Assessment of Citrate-Coated Calcium and Manganese Ferrite Nanoparticles for Magnetic Hyperthermia - Raquel G. D. Andrade; Débora Ferreira; Sérgio R. S. Veloso; Cátia Santos-Pereira; Elisabete M. S. Castanheira; Manuela Côrte-Real; Ligia R. Rodrigues (MDPI AG, 2022)
Calcium-doped manganese ferrite nanoparticles (NPs) are gaining special interest in the biomedical field due to their lower cytotoxicity compared with other ferrites, and the fact that they have improved magnetic properties. Magnetic hyperthermia (MH) is an alternative cancer treatment, in which magnetic nanoparticles promote local heating that can lead to the apoptosis of cancer cells. In this work, manganese/calcium ferrite NPs coated with citrate (CaxMn1−xFe2O4 (x = 0, 0.2, 1), were synthesized by the sol-gel method, followed by calcination, and then characterized regarding their crystalline structure (by X-ray diffraction, XRD), size and shape (by Transmission Electron Microscopy, TEM), hydrodynamic size and zeta potential (by Dynamic Light Scattering, DLS), and heating efficiency (measuring the Specific Absorption Rate, SAR, and Intrinsic Loss Power, ILP) under an alternating magnetic field. The obtained NPs showed a particle size within the range of 10 nm to 20 nm (by TEM) with a spherical or cubic shape. Ca0.2Mn0.8Fe2O4 NPs exhibited the highest SAR value of 36.3 W/g at the lowest field frequency tested, and achieved a temperature variation of ~7 °C in 120 s, meaning that these NPs are suitable magnetic hyperthermia agents. In vitro cellular internalization and cytotoxicity experiments, performed using the human cell line HEK 293T, confirmed cytocompatibility over 0-250 µg/mL range and successful internalization after 24 h. Based on these studies, our data suggest that these manganese-calcium ferrite NPs have potential for MH application and further use in in vivo systems.